Finnish berry juice as a DNA stain: the search for active DNA binding compounds capable of staining nucleic acids - Fotouhichianeh, Ziba (My University, 2025)
Many berries grown in Finland contain anthocyanins in high amounts, providing the berry juice a bright colour and capability to stain a variety of materials. On the basis of earlier studies on Finnish berry juice, it was established that the berry juice contains a substance (or substances) that has a capability to stain nucleic acids, and suggested anthocyanins as a candidate molecule(s). Historically, DNA visualization during electrophoresis has been done by the use of synthetic dyes such as ethidium bromide but considering their toxicity in the light of environmental perception, there is a need to search for safer, preferably natural, alternatives. This study addresses berry juice as a natural dye for the staining of nucleic acids, particularly DNA, in the context of gel electrophoresis. Thus, the aim of this study is to evaluate the feasibility of berry-derived substances as sustainable alternative DNA stain that can be used during gel electrophoresis in a non-toxic way. Further, the aim is to characterize the molecules that are responsible for the binding of DNA and thus are able to stain it. Frozen berries of Finnish origin were purchased from a grocery store and melted at room temperature. A filtered juice was obtained from unmashed, partially mashed, and totally mashed berries. Each juice preparation was used as a DNA dye in agarose gel electrophoresis, plasmid DNA acting as a probe. The above three berry juice preparations were also analyzed by the use of HPLC-DAD-ESI-MS/MS. Gel electrophoresis revealed substantial DNA staining only with the juice preparation from partially mashed berries. The stained plasmid DNA band in gel appeared purple under UV-light, similar to staining obtained with ethidium bromide. Based on the HPLC-DAD-ESI-MS/MS analysis, processed through MassLynx software, anthocyanins and proanthocyanidin appeared more stable in the partially mashed preparations and presumably were responsible for the clear and repeatable staining observed by gel electrophoresis. The DNA-staining molecule(s) from partially mashed berries most probably are anthocyanins, and their mode of staining presumably is intercalation. HPLC-DAD-ESI-MS/MS analysis of the three berry samples (unmashed, partially mashed, totally mashed) revealed a distinct variation in the amount of their compounds. These findings suggest that the extent of mechanical processing significantly influences the composition of DNA-binding compounds in the berry juice.
Keywords: Keyword: Finnish berry juice, anthocyanins, proanthocyanidins, DNA staining, mechanical processing, HPLC-ESI-MS/MS, gel electrophoresis